PERANAN BADAN NARKOTIKA NASIONAL PROVINSI RIAU DALAM MENANGGULANGI PEREDARAN NARKOTIKA DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Dani, Akbar; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Pekanbaru as one of the developing cities has a lot of charms in the field of social, economic and cultural. Pekanbaru as a developing city can not be separated from the rampant circulation of narcotics. Provincial National Narcotics Board (BNNP) Riau has a role to overcome the narcotics circulation, but the role of BNNP is always having problems. The purpose of thesis writing to determine the role of BNNP in overcoming the narcotics circulation and to determine the factors that cause the high circulation of narcotics in the city of Pekanbaru.This type of research can be classified in the type of research Sociological Juridical, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This study was conducted in the legal area of Penbaru City, whereas the population and sample are the whole parties related to the problems studied in this study, the data sources used, primary data, secondary data, and tertiary data, data collection techniques in this study by interview And literature review.From the results of research that the authors do can be concluded, the first Role of the National Narcotics Board of Riau Province in Tackling Narcotics Drugs in Pekanbaru City still not running maximally because to overcome the circulation of narcotics constrained funds for counseling or socialization conducted BNNP, and rehabilitation performed only succeed In the short term and the eradication carried out by BNNP is constrained due to lack of personnel in terms of both quality and quantity. The two factors causing the crime of narcotics circulation in Kota Pekanbaru are economic factors, environmental factors and educational factors.Keywords: Role-BNNP-Narcotics Circulation